Collective Asymmetric Total Synthesis of C‐11 Oxygenated Cephalotaxus Alkaloids. (16th April 2021) - Kim, Jae Hyun; Jeon, Hongjun; Park, Choyi; Park, Soojun; Kim, Sanghee
Abstract: While numerous studies pertaining to the total synthesis of Cephalotaxus alkaloids have been reported, only two strategies have been reported to date for the successful synthesis of the C‐11 oxygenated subset, due to the additional synthetic challenge posed by the remote C‐11 stereocenter. Herein, we report the collective asymmetric total synthesis of C‐11 oxygenated Cephalotaxus alkaloids using a chiral proline both as a starting material and as the only chirality source. A tetracyclic advanced intermediate was synthesized in a highly stereoselective manner from l ‐proline in 8 steps involving sequential chirality transfer steps such as a diastereoselective N ‐alkylation, stereospecific Stevens rearrangement and intramolecular Friedel–Crafts reaction via an unusual O ‐acyloxocarbenium intermediate. From a common intermediate, the asymmetric total synthesis of six C‐11 oxygenated Cephalotaxus alkaloids was completed by a series of oxidation state adjustments. Abstract : A collective asymmetric total synthesis of C‐11 oxygenated Cephalotaxus alkaloids was accomplished. This synthesis features sequential chirality transfer steps such as a diastereoselective N ‐alkylation, a stereospecific Stevens rearrangement and an intramolecular Friedel–Crafts reaction. A series of oxidation state adjustments from a common intermediate led to the asymmetric total synthesis of six C‐11 oxygenated Cephalotaxus alkaloids.